The Concept of Marxism happiness in China - Yun, Su; Muhammad Azizan Sabjan (Penerbit Universiti Kebangsaan Malaysia, 2024)
China has been the socialist country since 1949, when the new country was established. Communist Party of China (CPC) selected Marxism as the governing ideology for China which is consistent with the hierarchical and centre government system. CPC is dedicated to improving happiness of society for the citizens within the framework of Marxism ideology. However, the concept of Marxism happiness, and its development are still limited in terms of understanding and study. This paper explored the development of concept of Marxism happiness through the different works of Marx from his early writing to the authoritative academic book. The researcher then defined the concept of Marxism Happiness. This paper employs document analysis and thematic analysis to provide a clear understanding of the concept of Marxism Happiness and its implication for the happiness of Chinese citizens, meanwhile, it would be conducive to the researchers and policy makers in ideological construction of a country.